Poverty and adjustment: The case of Honduras - Jorge Navarro (CEPAL Review, 1993)
The impact of the structural adjustment process on the level of poverty has been a highly controversial issue in recent years. In this article, a macroeconomic approach is used to analyse the adjustment’s short-term effects on income levels, especially among the poor. Income has been chosen as the chief determinant of poverty levels because, in a market economy, income and related inflows are what determine how much control individuals have over the main factors influencing their living conditions. This variable is also quite elastic in respect of macroeconomic conditions and therefore reflects short-term effects.